Laboratory diagnosis of overt type 2 diabetes in the first trimester of pregnancy. Issue 9 (22nd June 2017) - Hessler, Karen L.; Dunemn, Kathleen
Abstract: Objective: The objective of this study was to compare the use of hemoglobin A1C to oral glucose tolerance testing to diagnose overt type 2 diabetes in the first trimester of pregnancy. The study used a nonexperimental descriptive design to compare the use of the hemoglobin A1C test results to oral glucose tolerance test results. Methods: The study used a sample of 45 women at high risk for type 2 diabetes in the first trimester of pregnancy. Participants were consented to draw a hemoglobin A1C with their ordered oral glucose tolerance testing for comparison of the two tests' ability to diagnose overt type 2 diabetes. Results: Hemoglobin A1C tests were highly positively correlated with oral glucose tolerance testing for diagnosis of type 2 diabetes in women in the first trimester of pregnancy. Conclusion: The research provides beginning evidence that the hemoglobin A1C should be considered as a first‐tier diagnostic test for overt type 2 diabetes in the first trimester of pregnancy.